PROCESSING OF BLACK SOLDIER FLY LARVAE AND SILKWORM AS FEED INGREDIENTS FOR SANGKURIANG CATFISH IN FISH FARMING GROUP IN PANGKALAN VILLAGE ACEH TAMIANG - Al Fajar, Beni; Wibowo, Sara Gustia; Hermawan, Tisna; Fitriani (Fakultas Teknik, Universitas Samudra, 2024)
The cost of feed consumption that continues to rise greatly affects the sustainability of cultivation activities, especially catfish cultivation. The partner in this service activity is a livestock group with the name Pangkal Ikan group. This group is domiciled in Pangkalan Village, kejuruan muda, Aceh Tamiang Regency, Aceh Province. Mitra focuses on hatchery, rearing and fattening Sangkuriang Catfish (Clarias gariepinus). The form of obstacles faced by partners today is factory-made feed which tends to be expensive and always rising and partners do not yet have the ability to cultivate silkworms and make feed independently. Therefore, this programs (PKM) is carried out to process alternative feed to replace commercial feed by utilizing maggot from black soldier flies (Hermetia illucens) or Black Soldier Fly (BSF) and silkworms (Tubifex sp) which are high in protein in reducing feed costs and increasing catfish production yields. . This service was carried out for 6 months with several stages, namely the preparation stage, socialization of the PKM program, training on the application of silkworm cultivation technology and processing BSF flies into pellet-shaped feed. Next, the operational assistance stage and ending with the evaluation monitoring stage. Based on the results of the activity shows that partners are very interested in the theme created. This can be seen from the enthusiastic involvement of partners in following and practicing directly silkworm cultivation techniques and pellet making techniques made from BSF fly maggots. In this activity, partners are fully involved directly so that later partners are able to practice the knowledge that has been given independently. It can be concluded that the implementation of the program is able to have a positive impact on partners who have been able to reduce feed costs.